Does a gender of Welwitschia mirabilis plants influence their photosynthetic activity? - Wiland-Szymańska, Justyna; Kazimierczak-Grygiel, Ewa; Drapikowski, Paweł; Borowiak, Klaudia; Drapikowska, Maria (PLOS ONE, 2023)
Welwitschia mirabilis Hook.f. (Welwitschiaceae, Gnetales) is a gymnosperm plant unique in its habit with an isolated taxonomic position. This species is dioecious, but no studies of its photosynthetic activity were conducted with examination of differences among male and female plants. To fill this gap, the day and night photosynthetic activity of male and female specimens of Welwitschia mirabilis cultivated in the botanical garden was studied in controlled conditions. Photosynthetic activity was studied using net photosynthetic rate (PN), stomatal conductance (gs) and intercellular CO2 concentration (Ci) parameters. Additionally, a normalized difference vegetation index (NDVI) was used to assess the condition among male and female plants in full sunlight. The studied Welwitschia plants revealed variability in photosynthetic activity both during the day and the night. The photosynthetic activity was low in the morning hours and higher in the afternoon. There is a difference in the photosynthetic activity during the night between sexes, being higher in female specimens. Stomatal density was evaluated separately for adaxial and abaxial leaf surfaces. Statistically significant differences in the stomatal density on abaxial and adaxial leaf surfaces were observed in both sexes, especially distinctive in female specimens. NDVI has revealed that there were weak differences between male and female plants.